Empreendimentos econômicos solidários: alternativas organizacionais de (re)inserção social e econômica - Gallo, Ana Rita (2003)
The conquests and benefits that the capitalist system provided to the society, in its historical-technological evolution, have been many. At the same time, that same system has been producting disadvantages, mainly, in relation to the labor that could not accompany its development. One of the factors that have promoted such situation was the technological, organizational and productive restructuring of the dominant organizations. Besides, the process of internationalization of the capital, the bad redistribution of the income, the precariousness of the work and life, have generated an economic inequality and an extremely serious social exclusion. From these considerations, it must be analyzed and understood the alternative organizational arrangements that exist inside of the capitalist system. The theory of the Post-modernity and the theory of the Solidary Economy, both in construction, have been the base of analysis of four studied organizational cases, denominated of Solidary Economic Enterprises (SEE). Those Enterprise, in their more common form, happen through the popular cooperatives. A particularity of this work is that two cases are urban and accompanied by an Incubator of Cooperatives linked to the Federal University of São Carlos, which are located in that same city; and two cases are rural, located in the Southwest area of the state of São Paulo and they link to the Landless Rural Workers Movement. The main objectives of the theory were: to analyze the life conditions and the work relationships in those enterprises; to understand the opportunities and limits that they face; and to understand them as an alternative of social (re)insert and of non precariousness of the work. Being a research of qualitative character, were used, as technique of data colletion, the following elements: mixed questionnaires, interviews, observations and documents analyses. The main results reveal that there is, through the urban and rural cooperartives, a real opportunity of economic and social (re)insert of the studied groups. However, there is a challenge to be faced in the sense of surpassing an organizational culture of little participation and building a culture of solidary cooperation.